Establishing a hepatitis C continuum of care among HIV/hepatitis C virus‐coinfected individuals in EuroSIDA. Issue 4 (8th February 2019) - Amele, S; Peters, L; Sluzhynska, M; Yakovlev, A; Scherrer, A; Domingo, P; Gerstoft, J; Viard, JP; Gisinger, M; Flisiak, R; Bhaghani, S; Ristola, M; et al.
Abstract : Objectives: The aim of the study was to establish a methodology for evaluating the hepatitis C continuum of care in HIV/hepatitis C virus (HCV)‐coinfected individuals and to characterize the continuum in Europe on 1 January 2015, prior to widespread access to direct‐acting antiviral (DAA) therapy. Methods: Stages included in the continuum were as follows: anti‐HCV antibody positive, HCV RNA tested, currently HCV RNA positive, ever HCV RNA positive, ever received HCV treatment, completed HCV treatment, follow‐up HCV RNA test, and cure. Sustained virological response (SVR) could only be assessed for those with a follow‐up HCV RNA test and was defined as a negative HCV RNA result measured > 12 or 24 weeks after stopping treatment. Results: Numbers and percentages for the stages of the HCV continuum of care were as follows: anti‐HCV positive ( n = 5173), HCV RNA tested (4207 of 5173; 81.3%), currently HCV RNA positive (3179 of 5173; 61.5%), ever HCV RNA positive ( n = 3876), initiated HCV treatment (1693 of 3876; 43.7%), completed HCV treatment (1598 of 3876; 41.2%), follow‐up HCV RNA test to allow SVR assessment (1195 of 3876; 30.8%), and cure (629 of 3876; 16.2%). The proportion that achieved SVR was 52.6% (629 of 1195). There were significant differences between regions at each stage of the continuum ( P < 0.0001). Conclusions: In the proposed HCV continuum of care for HIV/HCV‐coinfected individuals, we found major gaps at all stages, with almost 20% of anti‐HCV‐positive individuals having no documented HCV RNA test and a low proportion achieving SVR, in the pre‐DAA era.